Beta diversity of urban spontaneous plants and its drivers in 9 major cities of Yunnan province, China - Gao, Zhiwen; Pan, Yingji; Van Bodegom, Peter M.; Cieraad, Ellen; Xing, Dingliang; Yang, Yanyi; Xia, Tiyuan; Luo, Xinyi; Song, Kun; Da, Liangjun; Malkinson, Dan (Landscape and urban planning, 2023)
•The exponent (z) of the SAC model was used in urban ecosystems to characterize beta diversity.•We found the species composition of native plants was more heterogeneous than non-natives.•The beta diversity of all species groups was best explained by alpha diversity and urbanization.•Urban spontaneous plants diversity was determined by both the current state and historical processes of urbanization. Urbanization has significantly reshaped regional biodiversity structure globally. Previous studies suggested that urban communities of spontaneous plants are well adapted to the urban environment. However, a perspective of urbanization that accounts for the joint impacts of the current state (as expressed by urbanization intensity) and the historical progress of urbanization (as expressed by urbanization rate) to reveal the mechanisms underlying the biodiversity patterns of spontaneous plants in cities is still lacking. Here we present data and analysis of spontaneous plants sampled in 709 patches within 82 sites of built-up areas from nine cities distributed across climatic and floristic zones in Yunnan province, a biodiversity hotspot in China. We used the exponent (z) of a species accumulation curve (SAC) model to characterize beta diversity among patches in a site, and found a higher beta diversity of native species compared with non-natives, indicating that the species composition of native plants is more heterogeneous. The beta diversity of all species groups was best explained by the constant c of the SAC (a proxy of alpha diversity), followed by the urbanization intensity (as expressed by the proportion of sealed surface and patches’ Shannon diversity index), and urbanization rate (as expressed by the sealed surface expansion rate). Moreover, beta diversity of non-native species was additionally negatively correlated with altitude. Our results suggest that the interplay of natural environmental factors and human-induced urbanization shape diversity of urban spontaneous plants in Yunnan province. Our findings emphasize that urban spontaneous plants diversity is not only a reflection of the current state of urbanization, but also a consequence of historical processes of urbanization.